2014
DOI: 10.1111/cge.12388
|View full text |Cite
|
Sign up to set email alerts
|

Hypotrichosis‐lymphedema‐telangiectasia‐renal defect associated with a truncating mutation in the SOX18 gene

Abstract: SOX18 mutations in humans are associated with both recessive and dominant hypotrichosis-lymphedema-telangiectasia syndrome (HLTS). We report two families with affected children carrying a SOX18 mutation: a living patient and his stillborn brother from Canada and a Belgian patient. The two living patients were diagnosed with HLTS and DNA analysis for the SOX18 gene showed that both had the identical heterozygous C > A transversion, resulting in a pre-mature truncation of the protein, lacking the transactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…This variant is predicted to result in a protein truncated in size by 47%. Other pathogenic nonsense variants have been identified distal to the variant identified in this individual (Irrthum et al, ; Moalem et al, ; Valenzuela et al, ).…”
Section: Case Descriptionmentioning
confidence: 84%
See 4 more Smart Citations
“…This variant is predicted to result in a protein truncated in size by 47%. Other pathogenic nonsense variants have been identified distal to the variant identified in this individual (Irrthum et al, ; Moalem et al, ; Valenzuela et al, ).…”
Section: Case Descriptionmentioning
confidence: 84%
“…Although hypotrichosis is usually present at birth, Irrthum et al () reported an individual who did not develop hair loss until 6 months of age. Others with HLTS have developed alopecia universalis (Moalem et al, ). It is known that SOX18 is expressed in the hair follicles of humans and mice, and ragged mice had a notable privation of fur (Downes et al, ; Irrthum et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations